A Study on Vitality and Happiness Levels of Sports High School Students - Ömer Faruk Yazıcı; Mustafa Barış Somoğlu (Journal of Educational Issues, 2024)
The present study is aimed at determining subjective vitality and subjective happiness levels of sport high school students and to examine the levels based on certain variables. Relational screening model was used in this study. The sample of the research consisted of a total of 185 students, 113 (61.1%) male and 72 (38.9%) female, who continued their education at “Trabzon Sports High School” in 2019-2020. “Personal Information Form” designed by the researcher, “Subjective Vitality Scale (SVS)” and “Subjective Happiness Scale (SHS)” were used as data collection tools in the research. It was accepted that the research data showed a normal distribution according to the skewness and kurtosis values. Accordingly, descriptive statistics were used as a statistical method in the analysis of the data, and T-Test, one-way analysis of variance (ANOVA), correlation and regression analyzes were used for independent groups. In line with the research analysis, it was found that the students of sports high schools had above-average levels of vitality and happiness. It has been observed that the subjective vitality and happiness levels are higher among male students and students affiliated with a sports club (licensed/unlicensed). In addition, it was concluded that the subjective happiness and vitality levels are higher among students who do team sports and those who have longer years of practising sports, and no significant difference was determined according to the variable of socio-economic status of the family. As a result, it was found that there was a high (.81) significant positive correlation between subjective happiness and vitality. Another important result is that subjective vitality (66%) has an important role in predicting subjective happiness.